EFFECT OF COUNSELING TO KNOWLEDGE AND ATTITUDE OF GIRLS ABOUT DISMENORE AT TENTH GRADE OF MAN 5 JOMBANG TAHUN IN 2014 - Diah Erviana; Sri Sayekti; Anin Wijayanti (Jurnal Keperawatan, 2014)
Problem often faced by girls when menstruation comes was dismenore. In Indonesia, especially in East Java, Jombang, there are 9.678 girls who experienced dismenore. dismenore is a natural process that often occurs in every girl, but dismenore or menstrual pain can interfere daily activities. The purpose of this study was to know the effect of counseling toward knowledge and attitude of girls about dismenore. This type of study was experimental design with One group pre & post test, Population is all girls of tenth grade MAN 5 Jombang in 2014 as many as 55 girls, Sample of this study was 48 girls conducted with Proportionate random sampling technique. Independent variable was counseling about dismenore. Dependent variable was knowledge and attitude of girls about dismenore. Instrument used was a questionnaire. Data was processed through the stages of editing, coding, and scoring. To know the effect of counseling toward knowledge used Wilcoxon test and to know the effect of counseling toward attitude used Mc Nemar test. Result of Wilcoxon test, p = 0.000 (p <α) showed any effect between provision of counseling toward gilr’s knowledge about dismenore. Result of Mc Nemar test p = 0.013 (p <α) showed any effect of counseling toward girl’s attitude about dismenore. Based on the study result can be concluded that there was effect of counseling to knowledge and attitude of girls about dismenore at tenth grade of MAN 5 Jombang tahun in 2014.Keywords: Counseling, Knowledge, Attitude, Girls, dismenore